2017
DOI: 10.3390/f8060206
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Phosphorus Exports from a Small Forested Headwater-Catchment in the Eastern Ore Mountains, Germany

Abstract: Phosphorus (P) export from forest soils is mainly driven by storm events, which induce rapid flow processes by preferential flow bypassing large parts of the soil matrix. However, little is known about the dynamics, magnitude, and driving processes of P exports into surface waters. In this paper, we present the results of a monitoring study in a small forested catchment (21 ha) situated in the low mountain ranges of Saxony, Germany. During the fixed schedule-sampling (weekly to bi-weekly sampling frequency for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…After the installation of the samplers, the trenches and the soil above the samplers were covered with tarpaulins to simulate a dry summer period without rainfall of four weeks. According to Kaiser et al (2003), Julich et al (2017c), and other investigators, high-intensity rain events following a dry period have the highest potential for P translocations in forest soils.…”
Section: Sampler Design and Installationmentioning
confidence: 95%
See 1 more Smart Citation
“…After the installation of the samplers, the trenches and the soil above the samplers were covered with tarpaulins to simulate a dry summer period without rainfall of four weeks. According to Kaiser et al (2003), Julich et al (2017c), and other investigators, high-intensity rain events following a dry period have the highest potential for P translocations in forest soils.…”
Section: Sampler Design and Installationmentioning
confidence: 95%
“…However, recent studies have indicated that transport via preferential flow pathways might be crucial for P transport in and export from forest soils (Julich et al, 2017a;2017b). Correll et al (1999) and Julich et al (2017c) highlighted the link between storm events after dry periods and a significant rise of P concentrations in stream water, indicating that there are significant P losses from forest ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence and development of preferential flow in the soil are closely related to water, transport, and the accumulation of nutrients in the soil [57,58]. In this study, we used SPSS to calculate the soil nutrients and characteristic parameters of preferential flow to study the correlation between preferential flow and the accumulation of soil nutrients ( Table 7).…”
Section: Relationship Between Preferential Flow and Soil Nutrientsmentioning
confidence: 99%
“…Preferential flow, without conforming to Darcy's flow, is well recognized as a potentially important mechanism in soils [1][2][3]. This kind of flow can increase the leaching potential of soils and limit the storage, filter, and buffer functions of soils, and associate with a large number of inaccuracies in water and solute transport predictions [4][5][6][7][8][9][10]. Continuous root channels can generate preferential flow paths, and promote movement of water and solutes with little resistance [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%